Whole lymphoma B cells allow efficient cross-presentation of antigens by dendritic cells - Manches, Olivier (Informa Healthcare, 2008)
BACKGROUND: In order to compensate the paucity of defined tumor antigens in non-Hodgkin lymphomas, a promising approach might be the use of whole tumor cells as source of tumor antigens to pulse antigen-presenting cells. However, it is not presently known how the tumor cells should be delivered to antigen presenting cells to optimize the cross-presentation of tumor antigens to anti-tumor CD8 T cells. Here we aimed at comparing CD20-opsonized, apoptotic, and necrotic human tumor cells for their capacity to induce endocytosis and cross-presentation of tumor-associated antigens by dendritic cells or macrophages. METHODS: Endocytosis of human tumor-derived material by macrophages or dendritic cells was monitored by flow cytometry. We used the previously described influenza model and studied cross-presentation of viral antigens as cellular surrogate tumor-associated antigens by antigen-presenting cells after endocytosis of lymphoma B cells treated by inactivated influenza virus. RESULTS: Optimal endocytosis was obtained when tumor cells were opsonized by an anti-CD20 antibody, and as expected, macrophages were more phagocytic than dendritic cells. However, antigens from opsonized, apoptotic, and live cells but not from necrotic lymphoma cells were efficiently cross-presented by dendritic cells, but not by macrophages. DISCUSSION: We developed a new model with human primary lymphoma cells to study the cross-presentation of tumor-associated antigens by APCs. The results we obtained support the use of whole lymphoma cells from patient to pulse dendritic cells to induce antitumor immune response.